Importance of species traits on individual-based seed dispersal networks and dispersal distance for endangered trees in a fragmented forest - Li, Ning; Yang, Xifu; Ren, Yuanhao; Wang, Zheng (Frontiers in Plant Science, 2022)
Although mutualistic network analyses have sparked a renewed interest in understanding the patterns and drivers of network structures within communities, few studies have explored structural patterns within populations. In an endangered tree species population, plant individuals share their bird seed dispersers; however, little understanding of the factors affecting these individual interaction patterns has been provided. In this study, four individual-based networks were built for endangered Chinese yew, Taxus chinensis, in a fragmented forest based on bird foraging type (swallowing and pecking networks) and habitat type (network in bamboo patch and evergreen broad-leaved forest patch). With the results of species-level network metrics (species degree and specialization, d'), the effects of species traits (bird and plant traits) on species-level metrics in network and dispersal distance for T. chinensis were evaluated. It was revealed that the interaction network between T. chinensis individuals and their bird partners was influenced by bird foraging type and habitat of plant distribution. Compared to the other two networks, bird swallowing and bird–fruit networks in the evergreen broad-leaved patch habitat had higher nestedness and connectance but lower modules and specialization. Bird (body weight and wing and bill lengths) and plant traits (height, crop size, and cover) significantly affected species-level network metrics such as degree and specialization. Furthermore, seed dispersal distance was influenced by species traits and the species-level metrics of fruit–bird interaction networks. These results provide new insights into individual-based seed dispersal mutualistic networks of endangered plant species under habitat fragmentation. Moreover, these findings have relevant implications for conserving and managing individual endangered trees in increasingly disturbed ecosystems.